Cellular immune response of humans to the circumsporozoite protein of Plasmodium vivax - Mauricio M. Rodrigues; Araripe P. Dutra; Nobuko Yoshida (Memorias do Instituto Oswaldo Cruz, 1991)
The cellular immune response to the circumsporozoite (CS) protein of plasmodium vivax of individuals from malaria-endemic areas of Brazil was studied. We examined the in vitro proliferative response of the peripheral blood mononuclear cells (PBMC) of 22 individuals when stimulated with a CS recombinant protein (rPvCS-2) and two other synthetic peptides based on the sequenceof the P. vivax CS protein. Seven of the individuals from malaria-endemic area displayed an antigen specific in vitro proliferative responseto the recombinant protein PvCS-2 and one out of 6, proliferative response to the peptide 308-320. In contrast, none of the individuals displayed a proliferative reponse when stimulated with the D/A peptide which represent some of the repeated units present in this CS protein. Our study, therefore, provides evidence for the presence, withinthe major surface antigen of P. vivax sporozoites, of epitopes capble to induce proliferation of human PBMC.